2003
DOI: 10.1137/s0036139902416500
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Traveling Fronts in Lotka-Volterra Competition Models with Stage Structure

Abstract: This paper is concerned with a delay differential equation model for the interaction between two species, the adult members of which are in competition. The competitive effects are of the Lotka-Volterra kind, and in the absence of competition it is assumed that each species evolves according to the predictions of a simple age-structured model which reduces to a single equation for the total adult population. For each of the two species the model incorporates a time delay which represents the time from birth to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 9 publications
4
63
0
Order By: Relevance
“…Time delay may be used to model immature and mature stages; see [2] for an example. For the analysis of a system of delayed equations, we refer to [4]. More references can be found in the monograph of Kuang [81].…”
Section: Time-delayed Population Modelsmentioning
confidence: 99%
“…Time delay may be used to model immature and mature stages; see [2] for an example. For the analysis of a system of delayed equations, we refer to [4]. More references can be found in the monograph of Kuang [81].…”
Section: Time-delayed Population Modelsmentioning
confidence: 99%
“…Delays are often incorporated into population models for resource regeneration times, maturing times or gestation periods [6]. Gourley et al [1,7] considered reaction diffusion systems with delay terms. The system represents two interacting species for x ∈ (−∞, +∞), t ≥ 0, and the double convolution is defined by…”
Section: §1 Introductionmentioning
confidence: 99%
“…Gourley et al [1,7] presented a computational method for determining regions in parameter space corresponding to linear instability of a spatially uniform steady state solution. Similarly, for the variety of kernels, Beretta et al [2], Hasting [10], Yamada et al [14] discussed the corresponding models.…”
Section: §1 Introductionmentioning
confidence: 99%
“…Then using the fluctuation lemma and constructing sequences approaching equilibrium points we showed that the global stability of the equilibria in our model can be completely determined. The mathematical methods used in our proofs are inspired by AlOmari and Gourley's work [63]. By the study of the non-spatial system (3.1), we conclude that (i) the two interactive species with stage structure can persist in a stream; (ii) one species out-competes the other one, and the species cannot coexist; (iii) the two species can coexist and approach a stable population density in long term under certain conditions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…where There have been a number of investigations of traveling wave solutions and asymptotic behavior in terms of spreading speeds for various evolution systems including nonlinear reaction-diffusion systems [54,55,56] For a delayed Lotka-Volterra type competition model, Al-Omari and Gourley [63] showed that for c ≥c, wherec is some number, the system has a nondecreasing traveling wave solution connecting two mono-culture equilibria. Liang and…”
Section: Traveling Wave Solutionsmentioning
confidence: 99%